The Role of People's Banking Private Vocational (BPR) Toward Development of MSME in Lebak Banten - Agus Kusmana; Sumilir Sumilir (Universitas Mercu Buana, 2020)
This study aims to determine the role of BPR in the development of MSMEs. The research method uses a descriptive-qualitative analysis method. The population in this study are rural banks and MSMEs in the Lebak regency of Banten. The type of data used is secondary data and primary data The role of BPR in the development of MSMEs in the Lebak Regency of Banten with credit growth from 2016 - 2018 of 166.88% and MSME growth of 28.05%, the characteristics of MSME actors in the Lebak district of Banten is the age level of 40 -50 years and male sex with the majority of MSMEs married, and educated in high school, with experience managing businesses between 1 to 5 years, business characteristics, in general, financing customers of PT. BPR Lebak Sejahtera has a business in the field of handicraft, a self-owned business with a place of business that is also owned by itself, in running its business it already has an official business license. financing characteristics provided, the customer receives working capital financing with a repayment period of 1 to 3 years.